WORKSHOP KEPEMIMPINAN BERBASIS SYARIAH DI SMK 2 PATRIOT BEKASI - Tommy Kuncara; Erita Riski Putri; Abdul Muchlis; Sandy Suryady (Asosiasi Dosen Muda Indonesia, 2022)
Leaders are people who are entrusted with taking care of other people's affairs. Also referred to as Khadimul Ummah (servants of the people), that is, leaders must place themselves in the position of serving the community/company. Leaders must think of ways to make the company they lead progress, their employees prosper, and the environment around them to enjoy the presence of the company/group they lead. Meanwhile, sharia leadership is one that contains sharia aspects as a basic foundation in leading. The implementation of this community service activity was carried out at SMK 2 PATRIOT Bekasi. This activity was carried out using the teaching method with 2-way communication between the resource person and the participants. The results obtained in this activity are increased knowledge of students and teachers in terms of sharia-based leadership.